1977
DOI: 10.1002/ardp.19773101108
|View full text |Cite
|
Sign up to set email alerts
|

Die Triterpensäuren aus Coleus amboinicus Loureiro

Abstract: Ph 7941Aus den Blattern der siidamerikanischen Lamiacee Coleus amboinicus Loureiro werden 8 Triterpensauren isoliert. Hiervon werden 2 q 3Q-Dihydroxyoleanen-l7-saure, 2 q 3 q 19a-Trihydroxyursen-17-saure, 2~,3fl,l9~-Trihydroxyursen-l7-saure erstmals in Lamiaceen und wird 2q3q19Q-23-Tetrahydroxyursen-17-saure erstmals in einer Pflanze aufgefunden. Triterpenic Acids from Coleus Amboinicus LoureiroEight triterpenic acids have been isolated from the leaves of the South-American lamiaceae Coleus amboinicus Loureiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Compounds 17 and 24 were obtained from the Rosaceae family for the first time. The known compounds were identified as euscaphic acid (9) (Wang et al, 2003), 2-oxo-pomolic acid (10) (Wang et al, 2003), 18,19-seco,2a,3a-dihydroxyl-19-oxours-11,13(18)-dien-28-oic acid (11) (Huang et al, 2005), ursolic acid (12) (Wang et al, 2003), 1b-hydroxyeuscaphic acid (13) (Wang and Yuan, 2009), pinfaensic acid (14) (Durham et al, 1994), tormentic acid (15) (Wang et al, 2003), uvaol (16) (He et al, 2012), 3b-hydroxytaraxastan-28,20b-olide (17) (Errington and Jefferies, 1988), fupenzic acid (18) (Wang et al, 2003), pomolic acid (19) (Wang et al, 2003), annurcoic acid (20) (D'Abrosca et al, 2006), 2a,3a,19a,23-tetrahydroxyursolic acid (21) (Brieskorn and Riedel, 1977), swinhoeic acid (22) (Zhao et al, 2001), 1b-hydroxy-2-oxopomolic acid (23) (Ahn et al, 2012), 2a,3b-dihydroxyolean-11,13(18)-dien-19b,28-olide (24) (Lin et al, 2013), and 2a,3a-dihydroxyolean-12-en-28-oic acid (25) (Niu et al, 2013).…”
Section: Resultsmentioning
confidence: 98%
“…Compounds 17 and 24 were obtained from the Rosaceae family for the first time. The known compounds were identified as euscaphic acid (9) (Wang et al, 2003), 2-oxo-pomolic acid (10) (Wang et al, 2003), 18,19-seco,2a,3a-dihydroxyl-19-oxours-11,13(18)-dien-28-oic acid (11) (Huang et al, 2005), ursolic acid (12) (Wang et al, 2003), 1b-hydroxyeuscaphic acid (13) (Wang and Yuan, 2009), pinfaensic acid (14) (Durham et al, 1994), tormentic acid (15) (Wang et al, 2003), uvaol (16) (He et al, 2012), 3b-hydroxytaraxastan-28,20b-olide (17) (Errington and Jefferies, 1988), fupenzic acid (18) (Wang et al, 2003), pomolic acid (19) (Wang et al, 2003), annurcoic acid (20) (D'Abrosca et al, 2006), 2a,3a,19a,23-tetrahydroxyursolic acid (21) (Brieskorn and Riedel, 1977), swinhoeic acid (22) (Zhao et al, 2001), 1b-hydroxy-2-oxopomolic acid (23) (Ahn et al, 2012), 2a,3b-dihydroxyolean-11,13(18)-dien-19b,28-olide (24) (Lin et al, 2013), and 2a,3a-dihydroxyolean-12-en-28-oic acid (25) (Niu et al, 2013).…”
Section: Resultsmentioning
confidence: 98%
“…The second group was typical chemical shifts for pentacyclic triterpenes, for example signals of tertiary methyl group (appeared as singlet at δ 0.84, δ 0.88, δ 0.96, δ 1.12, and δ 1.16) and signals of an olefinic protons (around δ 5.00-δ 5.50). Indeed previous studies reported the presence of some flavonoids and triterpenes in this plant, such as oleanoic acid, ursolic acid, and maslinic acid (Brieskorn 1977;Brieskorn and Riedel 1977).…”
Section: Chemical Variability Of Indonesian Plectranthus Amboinicus Amentioning
confidence: 68%
“…The leaves are traditionally used as breast milk simulant (lactagogue) by Bataknese lactating women in North Sumatra (Damanik et al 2006). Many compounds have been identified from P. amboinicus leaves (Brieskorn 1977;Brieskorn and Riedel 1977). The antihyperglycemic (Viswanathaswamy et al 2011), and anti-inflammatory (El-Hawary et al 2012) potential of the plant extracts were reported.…”
Section: Introductionmentioning
confidence: 99%
“…limonene, ß-phellandrene, sabinene, limonene, biocyclogermacrene), flavonoids (e.g. quercertin) [12,13].…”
Section: Resultsmentioning
confidence: 99%